Geopolitik Politik Hukum RUU TNI/Polri: Antara Kepentingan Geopolitik dan Tekanan Masyarakat Sipil - nugrohooo, cahyo - (Maliki Interdisciplinary Journal, 2025)
The process of revising the Law on the Indonesian National Army (TNI) and the Indonesian National Police (Polri), known as the TNI/Polri Bill, has generated significant debate among the public. This relates to efforts to adapt the regulations to current security challenges, but also raises concerns about a possible return to ABRI's dual function practices that could reduce civilian control and threaten human rights. This article examines the legal politics of the revised TNI/Polri bill, focusing on the power dynamics between the state and society, and how this policy can strike a balance between the need for state stability and the demands for transparency and accountability in a democratic system. Through this analysis, the author provides suggestions for developing a legal framework that respects civil rights without compromising the effectiveness of national defense.